Ritual, rhetoric, and the polemic against the Host of Heaven - Quine, Cat (2019)
This study is an exploration of the theological and rhetorical potential of perceptions and proclamations of ritual failure, undertaken with specific regard to the polemic against rituals for the Host of Heaven. The Host of Heaven are a rare phenomenon within the Hebrew Bible: they occupy an accepted place within Yahwism in some texts (e.g., 1 Kgs 22:19-23; Neh 9:6; Ps 148:1-4) but are the targets of sustained polemic in others (e.g., Deut 17:3; 2 Kgs 21:3, 5; 23:4, 5; Jer 8:1-2). I contend that this phenomenon is best explained through the lens of ritual theory, especially theories of ritual failure. The biblical polemic is not against the Host of Heaven directly, but rather against those who practice rituals for them. These ritual practices are presented as threats to the cosmic and social order that disrupt the YHWH-Israel relationship and cause the downfall of the kingdoms of Israel and Judah and the deportation of the people. Ritual theory suggests that scrutiny of ritual is an inevitable and necessary consequence of these and other types of social upheaval; flawed and failed rituals must be identified and either corrected or discarded to re-stabilize the cosmic and social order. The Host of Heaven rituals were identified as flawed and failed rituals, responsible for causing social upheaval, and were polemicized against in response. The textualization of these polemics against the Host rituals resulted in the texts themselves becoming agents of ritual change, offering models of correct ritual practice. Once targets of ritual polemic, the Host became exemplary ritual practitioners — not worshipped themselves, but worshipping YHWH in the heavens (Pss 103:19-22; 148:1-4; Neh 9:6). This investigation offers ritual theory as an interpretive model for the study of these religious polemics in ancient Israel and Judah. In particular, it offers a conceptually coherent way of viewing developments in Israel’s faith that led to the rise of monotheism. Perceived ritual failure offered an opportunity for theological transformation and polemic against failed rituals was an important step in the journey toward a new, monotheistic ritual programme.